THE INFLUENCE OF SOCIAL MEDIA MARKETING ON CONSUMER TRUST IN ALLIANCE FRANCAISE MEDAN THROUGH CONSUMER SATISFACTION AS AN INTERVENING VARIABLE - Tengku Maura Safa Ramadhanti; Muhammad Alfikri (Journal Analytica Islamica, 2026)
The Universal Health Coverage (UHC) program is a strategic policy to ensure equitable access to health services, but its effective implementation still faces communication challenges, particularly the low public understanding of the benefits, procedures, and mechanisms of the service. This study aims to analyze the persuasive communication strategy of the Public Relations of the North Sumatra Provincial Health Office in designing and delivering UHC socialization messages. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results show that the public relations implemented a persuasive strategy through simplifying technical messages, using rational and emotional approaches, utilizing face-to-face communication and digital media, and adapting language to the socio-cultural characteristics of the community. These strategies contributed to increasing public understanding and trust in the UHC program, despite still being hampered by health literacy, access to information, and misinformation. The novelty of this study lies in its emphasis on the persuasive message design patterns of local government public relations in public health communications. These findings provide practical contributions for government agencies in designing UHC communications that are more adaptive, inclusive, and based on community needs.